Impact of corvitin and alpha-ketoglutarate on heart morphology, expression and activity of matrix metalloproteinases 2/9 in the heart of rats with doxorubicin-induced cardiomyopathy - I. A. Gordiienko; O. V. Poslavska; A. I. Shevtsova (Regulatory Mechanisms in Biosystems, 2019)
The anthracycline anticancer drug doxorubicin is an effective and frequently used chemotherapeutic agent for various malignancies but it causes acute ventricular dysfunction, and also induces cardiomyopathy and heart failure. One of the mechanisms of cardiotoxicity of doxorubicin is oxidative stress, which stimulates myocardial remodeling. Matrix metalloproteinases MMP2 and MMP9 play a key role in this process. Despite extensive research, the expression and activity of these enzymes in the doxorubicin-damaged heart and the effect of antioxidants on these indicators have not been sufficiently studied. The aim of this work was to study the possible cardioprotective effect of the antioxidant drugs corvitin and alpha-ketoglutarate in rats with doxorubicin-induced cardiomyopathy. Cardiomyopathy in rats was induced by intraperitoneal administration of doxorubicin at the dose of 2.5 mg/kg body weight weekly for 28 days. Animals were divided into four groups: group 1 (control) received saline injections (2.5 mL/kg); group 2 – injections of doxorubicin, 3 – corvitin (5 mg/kg) 60 minutes before doxorubicin administration, 4 – doxorubicin and 1% solution of alpha-ketoglutarate in drinking water ad libitum. Heart weight and shape indexes, the ratio of muscle to connective tissues, and heart histology were examined 7 days after the end of drug administration. Activity of MMP2 and MMP9, their intracellular distribution in myocardial tissues were evaluated by gelatin-zymography and immunohistochemistry. It was found that doxorubicin cardiomyopathy in rats was accompanied by a decrease in heart weight index, adaptive change of heart shape from ellipsoid to globular, increase of connective tissue content. Administration of doxorubicin results in profound lesion of the cardiomyocytes of the atria and ventricle, manifested by excessive cytoplasmic expression of MMP2 and MMP9 and an increase their activity in the heart. Antioxidants corvitin and alpha-ketoglutarate have insufficient regenerative effect on mass and shape indexes of heart however, exhibit potent cardioprotective effect by regulation of expression and activity of MMP2 and MMP9.